Optimal board independence with gray independent directors - Bartolomé Pascual-Fuster; Rafel Crespí Cladera (BRQ Business Research Quarterly, 2022)
Based on the optimal board independence theory, we analyze how Spanish listed firms determine the presence of genuine and gray independent directors. We classify independents as gray whenever they do not satisfy formal independence requirements. Given the findings in previous literature, this type of gray independent does not promote poor corporate governance practices. Our results suggest that the presence of gray and genuine independent directors is related to the optimal board independence determinants as if both provided real board independence. Results are not affected by the number and the type of unsatisfied independence criteria, nor by the firm's achievement of regulators' recommended level of board independence. Therefore, we conclude that firms pay little attention to formal independence requirements to reach their optimal board structure.
Keywords: G30; G34; K22; 650; Corporate governance; gray board independence; optimal board independence; formal independence requirements